2-Dodecyl-6-Methoxycyclohexa-2,5-Diene-1,4-Dione Isolated from Averrhoa carambola L. Root Ameliorates Diabetic Nephropathy by Inhibiting the TLR4/MyD88/NF-κB Pathway [Corrigendum] - Lu S (Dove Medical Press, 2020)
Lu S, Zhang H, Wei X, et al. Diabetes Metab Syndr Obes.  2019;12:1355– 1363. The authors have advised Figure 7 on page 1360 is incorrect. Due to an error at the time of figure assembly NC and H in the TLR4-/-groups row were duplicated. The correct Figure 7 is shown below. The authors apologize for this error and advise it does not affect the results of the paper. Read the original article